The role of supercritical carbon dioxide for recovery of shale gas and sequestration in gas shale reservoirs. Issue 8 (21st April 2021) - Lyu, Qiao; Tan, Jingqiang; Li, Lei; Ju, Yiwen; Busch, Andreas; Wood, David A.; Ranjith, Pathegama Gamage; Middleton, Richard; Shu, Biao; Hu, Chenger; Wang, Zhanghu; Hu, Ruining
Abstract : This review summarizes the potential and challenges of supercritical carbon dioxide (SC-CO2 ) enhanced shale gas recovery and sequestration in shale reservoirs. Abstract : The development of hydraulic fracturing and horizontal drilling techniques has promoted the exploitation of shale gas resources. However, using water has several potential drawbacks including environmental issues, e.g., the contamination of groundwater, surface water, and soil. Supercritical carbon dioxide (SC-CO2 ), with its special physical properties, has shown potential to enhance shale gas recovery replacing water as the stimulation fluid. This review summarizes the current status of shale gas recovery, the potential role of SC-CO2 as a working fluid for shale gas recovery, and CO2 geological sequestration in shale reservoirs. SC-CO2 has a better rock-breaking capability than water, which is useful when drilling through shale formations. SC-CO2 fracturing creates rougher and more complex fracture networks than hydraulic fracturing, leading to higher permeabilities. Some of the injected CO2 for shale gas recovery could also be safely sequestered in shale reservoirs, thereby lowering carbon emissions and accessing CO2 tax credits. However, shale–CO2 or shale–water/brine–CO2 interactions during & after shale gas recovery and sequestration can affect reservoir properties. The implied shale–CO2 imbibition process from available data generally persists for several years, far more than the several days assumed for most laboratory tests. A more detailed understanding is required for SC-CO2 injection on the efficiency of shale gas recovery and the cost and environmental concerns of this technology. This will support the development of safe sequestration methods, supported by suitable laboratory and field tests, especially those focusing on geochemical, petrophysical, geomechanical and hydraulic properties.